Sjukepleiaren si kompetanseutvikling i kommunehelsetenesta; samspel mellomutdanningsinstitusjon og arbeidsplass - Hovland, Gro; Kyrkjebø, Dagrun; Råholm, Maj-Britt (Nordisk Tidsskrift for Helseforskning, 2015)
Nurses’ competence development in municipal health services – Interactions between nursing school and work place Due to recent reforms, the increased requirements within comprehensive health care services, such as patients with complex and multiple diseases, need to be met by the municipalities. Nurses, thus need to increase their competence in accordance with the changes in municipal health services. The purpose of this study is to gain knowledge about the nurses’ daily work with a focus on learning and competence development. Data were collected by use of focus group interviews and analysed using qualitative content analysis. Findings demonstrate that nurses do not receive the appropriate training and experience needed to handle emergency situations. The lack of training causes uncertainty, which is not recognized by their superiors. Findings indicate that nursing schools need to be in closer dialogue with their students’ workplaces, both in planning and during their education.